Appropriateness to set a group health based guidance value for nivalenol and its modified forms. (19th April 2017) - ,; Knutsen, Helle Katrine; Barregård, Lars; Bignami, Margherita; Brüschweiler, Beat; Ceccatelli, Sandra; Cottrill, Bruce; Dinovi, Michael; Edler, Lutz; Grasl‐Kraupp, Bettina; Hogstrand, Christer; Hoogenboom, Laurentius (Ron); et al.
Abstract: The EFSA Panel on Contaminants in the Food Chain (CONTAM) reviewed new studies on nivalenol since the previous opinion on nivalenol published in 2013, but as no new relevant data were identified the tolerable daily intake (TDI) for nivalenol (NIV) of 1.2 μg/kg body weight (bw) established on bases of immuno‐ and haematotoxicity in rats was retained. An acute reference dose (ARfD) of 14 μg/kg bw was established based on acute emetic events in mink. The only phase I metabolite of NIV identified is de‐epoxy‐nivalenol (DE‐NIV) and the only phase II metabolite is nivalenol‐3‐glucoside (NIV3Glc). DE‐NIV is devoid of toxic activity and was thus not further considered. NIV3Glc can occur in cereals amounting up to about 50% of NIV. There are no toxicity data on NIV3Glc, but as it can be assumed that it is hydrolysed to NIV in the intestinal tract it should be included in a group TDI and in a group ARfD with NIV. The uncertainty associated with the present assessment is considered as high and it would rather overestimate than underestimate any risk.